Hak Asuh Anak Pasca Perceraian Dalam Perspektif Hukum Keluarga Islam: Studi Di Kabupaten Pangkep - Sikra, Sikra; Muchsin, Agus; Rusdi, Ali; Hannani, Hannani; Rahmawati, Rahmawati (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
This study analyzes post-divorce child custody as an important aspect in the context of Islamic family law. This article examines various aspects of post-divorce child custody, focusing on the Islamic legal framework. Through an analysis of the perspective of Islamic family law, this article discusses the rights and obligations of parents towards children, the role of the court in determining custody, and the principles that guide the post-divorce child custody process. This study aims to provide an in-depth understanding of the concepts of Islamic family law related to child custody, and their implications for child welfare in divorce situations. The method used in this study is a qualitative method with data collection used, namely data by collecting from the results of observations, documentation, and interviews. The results of the study obtained are the implementation of child custody after divorce in Pangkep Regency in reality does not comply with the decision of the Religious Court with the existence of obstacles, obstacles in the Implementation of Child Custody After Divorce in Pangkep Regency are as follows: Lack of sense of responsibility of the mother, the mental condition of the mother who is not ready to face divorce, lack of religious knowledge of the mother and the solution to these obstacles is: providing an understanding to the mother of a sense of responsibility that the child is a trust from Allah and will be accounted for, providing an understanding that not every divorce has a negative impact, increasing religious understanding that Allah has predestined divorce. The conclusion of this article provides insight into how Islamic family law regulates child custody after divorce by considering legal aspects, ethics, and the best interests of the child.